Antioxidative Properties of White Saffron Extract (Curcuma mangga Val) in The B-Carotene Bleaching and DPPH-Radical Scavenging Methods - Dwiyati Pujimulyani; Agung Wazyka; Sri Anggrahini; Umar Santoso (Indonesian Food and Nutrition Progress, 2004)
Study on antioxidative properties of white saffron extract in the emulsion system of b-carotene linoleic acid (b-carotene bleaching method) and DPPH-radical scavenging method was undertaken. The objective of this study was to examine the antioxidative activity of white saffron extract in the emulsion system of b-carotene linoleic acid and for radical scavenging activity by DPPH method. The extraction was carried out as follows: fresh white saffron was peeled and blanched in the 0.5% boiling citric acid solution for 5 minutes, the blanched white saffron was grated, and added distilled water. The ratio between grated white saffron and distilled water were 1 : 1 ; 1 : 2 ; 1 : 3, and 1 : 4. The mixture was then mannually filtered through cloth to obtain white saffron extract. The antioxidant acttvity of white saffron extract was evaluated in the emulsion system of b-carotene linoleic acid and DPPH- radical scavenging method with reference standard of Butylated Hydroxy Anisole (BHA) and linoleic acid with no while saffron extract as a control. The results of this study showed that the oxidative inhibition of white saffron extract in the emulsion system of â-carotene linoleic acid was not significantly different from to BHA 200 ppm. The lower ratio of grated white saffron and distilled water, the lower percent free radical scavenging capacity. The higher white saffron extract concentration (white saffron : distilled water = 1: 2) the higher percent free radical scavenging capacity.